2018
DOI: 10.1111/apha.13067
|View full text |Cite
|
Sign up to set email alerts
|

A selenoprotein T‐derived peptide protects the heart against ischaemia/reperfusion injury through inhibition of apoptosis and oxidative stress

Abstract: These results unravel the role of SelT as a cardiac modulator and identify PSELT as an effective pharmacological post-conditioning agent able to protect the heart after ischaemic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 68 publications
(141 reference statements)
7
91
0
Order By: Relevance
“…These transfusions are repeatedly discussed as risk factors for complications like necrotizing enterocolitis, intraventricular haemorrhage, retinopathy of prematurity, thrombotic events and sepsis . In preclinical studies, PHDi are currently investigated for their beneficial potential in diverse animal models of ischaemia, for example, preconditioning against ischaemia‐reperfusion injury in kidney, heart, brain, muscle and liver . This preconditioning effect of PHDis might be extremely useful for the quality of donor organs prior to transplantation.…”
Section: Which Other Clinical Applications Can We Think Of?mentioning
confidence: 99%
“…These transfusions are repeatedly discussed as risk factors for complications like necrotizing enterocolitis, intraventricular haemorrhage, retinopathy of prematurity, thrombotic events and sepsis . In preclinical studies, PHDi are currently investigated for their beneficial potential in diverse animal models of ischaemia, for example, preconditioning against ischaemia‐reperfusion injury in kidney, heart, brain, muscle and liver . This preconditioning effect of PHDis might be extremely useful for the quality of donor organs prior to transplantation.…”
Section: Which Other Clinical Applications Can We Think Of?mentioning
confidence: 99%
“…Also waste and waste substances can lead to multiple pathologies including different types of cancer. 3 Beside the protective role of selenium for cancer, a recent study showed that a novel thioredoxin-like enzyme selenoprotein T has cardio-protective properties especially after ischaemia/reperfusion injury. 1 Other possible risk factors are just associated with the development of cancer like the deficiency of selenium.…”
mentioning
confidence: 99%
“…2 Some of the reasons for cancer are already studied very extensively like the consumption of tobacco which is responsible for around 22% of cancer deaths and infections such as hepatitis and human papilloma virus being responsible for 25% of cancer cases. 3,4 The auxiliary subunit α 2 δ of voltage-gated Ca 2+ channels is also associated with cancer. Selenium is an essential trace element incorporated in at least 25 selenoproteins which have antioxidant activity among other effects.…”
mentioning
confidence: 99%
“…In this issue of Acta Physiologica, Rocca et al uncover a new role for selenoprotein T (SelT or SELENOT) as a potential modulator of cardiac damage and highlight the ability of a SelT mimetic peptide to improve heart function following ischaemia/reperfusion (I/R) injury. Selenium is an essential trace element, which can be incorporated into proteins as a selenocysteine (Sec) residue.…”
mentioning
confidence: 99%
“…However, its exact function, particularly in adult tissues, remains unknown. Rocca et al show that while SelT expression is undetectable in the adult heart under normal physiological conditions, the expression of this selenoprotein is dramatically increased following ischaemia/reperfusion (I/R) injury. Importantly, they show that a SelT‐derived peptide, SelT 43‐52 (PSELT), which contains the catalytic Sec residue, can protect the heart from I/R injury.…”
mentioning
confidence: 99%